Application Of Spatio-Temporal Remote Sensing Data Analysis in Fire Monitoring - Chen, Yizhou (Transactions on Environment, Energy and Earth Sciences, 2024)
This paper investigates the application of spatio-temporal remote sensing data analysis in fire monitoring, aiming to cope with the increase in the frequency of forest fires and its threat to the ecological environment and human security due to global warming and increased human activities. The study describes the application of various remote sensing techniques in fire monitoring, including Moderate Resolution Imaging Spectroradiometer (MODIS) satellite data, infrared remote sensing, satellite hyperspectral data, and SAR techniques. The application of remote sensing data in actual fire monitoring was demonstrated through case studies of the "330 forest fire" in Muli County, Sichuan Province, and the boreal forest fire in Canada. The integration of multi-source satellite remote sensing data can improve the timeliness of monitoring and avoid the interference of complex environments, thus reducing disaster losses. This paper argues that remote sensing technology has a broad development prospect in forest fire monitoring and that the accuracy and timeliness of monitoring can be improved by further integrating GIS, innovative technologies, and algorithmic applications. The future challenge lies in strengthening the integration of remote sensing technology and GIS to enhance data processing capability and disaster prediction accuracy to provide more effective support and assurance.